Characterization of early stage cartilage degradation using diffuse reflectance near infrared spectroscopy. - Brown, C; Jayadev, C; Glyn-Jones, S; Carr, A; Murray, D; Price, A; Gill, H (2011)
Interest in localized and early stage treatment technologies for joint conditions such as osteoarthritis is growing rapidly. It has therefore become important to develop objective measures capable of characterizing the earliest (non-visible) changes associated with degeneration to aid treatment procedures. In addition to assessing tissue before treatment, it is further important to develop an effective, non-destructive means of monitoring post-treatment tissue healing, and of providing the high-quality data needed for trials of developing treatment methods. To investigate its ability to detect the early stages of degeneration in cartilage-on-bone, diffuse reflectance near infrared spectroscopy was applied to normal and osteoarthritic joints. A discriminating function was developed to relate absorbance peaks of interest and track degradation around focal osteoarthritic defects. The function could distinguish between normal and degraded tissue (100% separation of normal tissue from that within 25 mm of a defect) and between different stages of osteoarthritic progression (p < 0.05). This technique allows simple, practical and non-destructive assessment of component-level properties over the full depth of the tissue. It has the potential to increase our understanding of the underlying etiologic and pathogenic processes in early stage degeneration, to assist classification and the development of new treatment methods.